1994
DOI: 10.1007/s00585-994-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and distribution patterns of snow and meteoric ice in the Weddell Sea and their contribution to the mass balance of sea ice

Abstract: Abstract. Based on snow- and ice-thickness measurements at >11 000 points augmented by snow- and icecore studies during 4 expeditions from 1986 - 92 in the Weddell Sea, we describe characteristics and distribution patterns of snow and meteoric ice and assess their importance for the mass balance of sea ice. For first-year ice (FY) in the central and eastern Weddell Sea, mean snow depth amounts to 0.16 m (mean ice thickness 0.75 m) compared to 0.53 m (mean ice thickness 1.70 m) for second-year ice (SY) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
175
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(196 citation statements)
references
References 0 publications
18
175
3
Order By: Relevance
“…More importantly, based on earlier observations by Lange and Eicken (1991), Eicken et al (1994), and Lytle and Ackley (1996), we were expecting the widespread occurrence of negative ice freeboard as a result of thick snow depressing the snow/ice interface below the seawater level. Drill holes would irreversibly cause seawater to flush onto the ice surface if the ice had not yet been flooded for natural reasons (as observed during ISPOL, see below).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…More importantly, based on earlier observations by Lange and Eicken (1991), Eicken et al (1994), and Lytle and Ackley (1996), we were expecting the widespread occurrence of negative ice freeboard as a result of thick snow depressing the snow/ice interface below the seawater level. Drill holes would irreversibly cause seawater to flush onto the ice surface if the ice had not yet been flooded for natural reasons (as observed during ISPOL, see below).…”
Section: Introductionmentioning
confidence: 94%
“…While drilling provides the most accurate ice and snow thickness estimates (e.g., Lange and Eicken, 1991;Eicken et al, 1994), the method is limited by its slow progress, in particular on thick second-year ice, preventing the acquisition of long profiles spanning and demarcating regions of different ice types. More importantly, based on earlier observations by Lange and Eicken (1991), Eicken et al (1994), and Lytle and Ackley (1996), we were expecting the widespread occurrence of negative ice freeboard as a result of thick snow depressing the snow/ice interface below the seawater level.…”
Section: Introductionmentioning
confidence: 99%
“…At larger scales, estimation of snowfall amounts on sea ice have been inferred from atmospheric reanalysis products [e.g., Bromwich et al, 1995;Maksym and Markus, 2008], which have not been directly validated over sea ice. Such estimations also fail to account for the amount of blowing and drifting snow that is actually lost to open water between ice floes (leads), which can amount to a significant portion of the total yearly mass balance [Eicken et al, 1994;Leonard and Maksym, 2011]. Eicken et al [1994] estimated that as much as 100 mm yr À1 was lost to leads from data from the Weddell Sea; however, there are scarce observations to better address this question over larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…Such estimations also fail to account for the amount of blowing and drifting snow that is actually lost to open water between ice floes (leads), which can amount to a significant portion of the total yearly mass balance [Eicken et al, 1994;Leonard and Maksym, 2011]. Eicken et al [1994] estimated that as much as 100 mm yr À1 was lost to leads from data from the Weddell Sea; however, there are scarce observations to better address this question over larger scales. Similarly, Dery and Tremblay [2004] estimated that as much as 30% of annual snowfall was lost through sublimation of blowing snow, based on their observations during the Surface Heat Budget of the Arctic Ocean (SHEBA) experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies Sturm et al, 1998] have found that the constantly changing synoptic conditions and the redistri- , 1975]. The ocean heat flux can play a critical role in determining the thermodynamic limit to which the ice will grow, the amount of snow-ice that may form [Eicken et al, 1994], and the ice melt rate in the spring. In this study we report on calculations of ocean heat flux Qo and its influence on the sea ice thickness in the region.…”
Section: Introductionmentioning
confidence: 99%